Comparison of maternal anxiety scores in pediatric intensive care unit and general ward parents - Lie Affendi Kartikahadi; Soetjiningsih Soetjiningsih; I Gusti Ayu Endah Ardjana; I Gusti Ayu Trisna Windiani (Indonesian Pediatric Society Publishing House, 2012)
Background Hospitalization of a child is known to be a dreadful and stressful situation for parents. One study reported that admitting a child to a general ward caused mild anxiety to mothers, while admitting a child to the pediatric intensive care unit (PICU) caused moderate anxiety to mothers. Objective To compare Hamilton anxiety scores of mothers whose children were admitted to the PICU to those of mothers whose children were admitted to the general ward. Methods A cross-sectional study was done on mothers of children aged 1 month-12 years. Children were admitted to either the intensive care unit or the general ward from October 2010-January 2011. All subjects were assessed by Hamilton anxiety scores and questioned for risk factors and other causes of maternal anxiety. Consecutive sampling was used to allocate the subjects. Differences were considered statistically significant for P < 0.05. Results Of the 72 subjects, the median Hamilton anxiety score in mothers of children admitted to the PICU was 20.5 (interquartile range 14-29.75), higher than that of mothers of children admitted to the general ward (14, interquartile range 9-16.75). MannWhitney U test revealed a statistically significant difference in scores between the two groups (P = 0.DO1). Ancova multivariate analysis showed the admission location to be the only significant relationship to Hamilton anxiety score (P = 0.0001). Conclusion Hamilton anxiety scores were higher for mothers of children admitted to the PICU than that of mothers with children admitted to the general ward. [Paediatr lndones. 2012;52:95-8].